Hitchcock's blondes : the unforgettable women behind the legendary director's dark obsession - Leamer, Laurence (G.P. Putnam's Sons, 2023)
Offering an intimate journey into the lives of eight legendary actresses whose stories help chart the course of the enigmatic director's career, this mesmerizing account takes a modern look at both the enduring art created by a man obsessed-and the private toll that fixation took on the women in his orbit.